Transformasi Pemasaran Menggunakan Kecerdasan Buatan (AI) Untuk Mendorong Kemajuan UMKM Di Aceh Bireuen (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
In the digital era, Micro, Small, and Medium Enterprises (MSMEs) in Aceh-Biruen face challenges in developing effective marketing strategies. This study aims to analyze the potential of marketing transformation through the utilization of artificial intelligence (AI) as an innovative approach to enhance MSMEs' performance and competitiveness. The research employs a mixed-method approach, including field surveys, in-depth interviews, and comparative analysis involving 40 MSME stakeholders. The results show that AI can optimize market segmentation, improve consumer needs prediction, and create more accurate marketing strategies. MSMEs integrating AI into their marketing strategies reportedly increase sales by up to 35%, expand market reach, and reduce marketing costs. However, challenges such as limited technical knowledge and access to capital and digital infrastructure persist. This study concludes that integrating AI into MSME marketing holds significant potential to support digital transformation in Aceh-Biruen, offering practical recommendations for the government and stakeholders to promote innovation in the MSME sector.